Long-term Response to Nivolumab and Acute Renal Failure in a Patient with Metastatic Papillary Renal Cell Carcinoma and a PD-L1 Tumor Expression Increased with Sunitinib Therapy: A Case Report - Ruiz-Bañobre, Juan; Anido, Urbano; Abdulkader, Ihab; Antúnez-López, José; López-López, Rafael; García-González, Jorge (Frontiers in Oncology, 2016)
Introduction Papillary renal cell carcinoma (PRCC), which represents around 20% of renal cell carcinomas, is a heterogeneous disease that includes different tumor types with several clinical and molecular phenotypes. Nivolumab, a fully human IgG4 programed cell death protein 1 immune checkpoint inhibitor antibody, has shown not only an overall survival advantage when compared to everolimus but also a relatively good side-effect profile among patients with previously treated advanced or metastatic renal cell carcinoma. Case report We describe a case of a young man diagnosed with PRCC that achieved a durable response to nivolumab despite a temporary suspension of the treatment due to a renal function side effect. To the best of our knowledge, it is the first renal failure secondary to nivolumab in a metastatic renal cell carcinoma patient. Concluding remarks Nivolumab is a promising drug in patients with metastatic PRCC and long-term responses can be achieved. In case of acute renal failure secondary to this treatment, temporary therapy suspension and a low dose of systemic corticosteroids can recover renal function without a negative impact on treatment efficacy.